Left Ventricular Hypertrophy in Borderline and Low-Grade Hypertension: A Narrative Review - Gaprindashvili, Tamar; Agladze, Rusudan; Bochorishvili, Inga; Pagava, Zurab (Universitas Airlangga, 2026)
Left ventricular hypertrophy represents a major response to hypertension that is considered adaptive and is accompanied by cardiac structural and functional remodeling. This focused narrative review integrates data from 26 different references and studies concerning clinical aspects of LVH in borderline and low-grade hypertension. Among the 26 reviewed studies, 6 cohort analyses reported LVH prevalence in borderline hypertension and stage 1 hypertension. It was revealed that echocardiography demonstrated four times greater sensitivity for detecting LVH compared to ECG criteria. At the same time, LVH regression with RAAS inhibitors reduced cardiovascular risk. Emerging tools like speckle-tracking echocardiography and cardiac MRI provided earlier and more precise detection of subclinical LVH. Findings include the independent association of LVH with cardiovascular morbidity/mortality, the importance of myocardial ischemia in adverse outcomes, and the regression of LVH through specific therapeutic interventions. Discussion also includes new information concerning genetic predisposition, molecular pathways, and other advancements in diagnosis. – Highlights: 1. This review highlights the diagnostic gap in detecting LVH among borderline and stage 1 hypertensive patients. It was found that echocardiography offered roughly four times greater sensitivity than standard ECG, with speckle-tracking echocardiography further identifying subclinical strain abnormalities in patients without overt LVH. 2. It was found that RAAS inhibitors (particularly ARBs) produced the greatest reductions in left ventricular mass, and that LVH regression was associated with a 40% lower risk of major adverse cardiovascular events.